Nonlinear optical properties of meso-Tetra(fluorenyl)porphyrins peripherally functionalized with one to four ruthenium alkynyl substituents. (April 2021) - Zhang, Xu; Shi, Limiao; Fox, Mark A.; Barlow, Adam; Morshedi, Mahbod; Cifuentes, Marie P.; Humphrey, Mark G.; Mongin, Olivier; Paul, Frédéric; Paul-Roth, Christine O.
Abstract: The synthesis of a series of four porphyrin derivatives based on a meso -tetrafluorenylporphyrin core functionalized with one to four trans -chlorobis(dppe)ruthenium alkynyl units (dppe = 1, 2-bis(diphenylphosphino)ethane) at the periphery, together with cyclic voltammetry (CV) and UV–Vis absorption and emission spectroscopy studies, are reported. In these multipolar assemblies, the organoruthenium endgroups are potential electron-donors and the central porphyrin core is a potential electron-acceptor. The third-order nonlinear optical (NLO) responses have been assessed by Z-scan, revealing that these extended π-networks incorporating polarizable organometallic units behave as nonlinear absorbers in the near-IR range. The role of the peripheral transition metal centers on the third-order NLO properties is discussed. Graphical abstract: Peripheral Functionalization with Electron-rich Ru(II) Alkynyl Substituents Improves the Nonlinear Absorption Properties of meso -Tetra-Fluorenyl Porphyrins Free-bases in the Near-IR Range. Image 1 Highlights: New tetra(fluorenyl) free-bases porphyrins with trans -RuCl(dppe)2 alkynyl complexes on their peripheral positions are reported. The peripheral organometallic endgroups are only weakly electronically coupled through the porphyrin core in the ground state. The complete series exhibits sizeable nonlinear absorption properties extending intothe near-IR range. The effective two-photon absorption cross-sections in the near-IR range are proportional to the number of metallic centres present at their periphery. A rationale is proposed for explaining the physical origin of these nonlinear absorptions.